2004
DOI: 10.1161/01.atv.0000106320.40933.e5
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Monocyte Complexes Support Monocyte Adhesion to Endothelium by Enhancing Secondary Tethering and Cluster Formation

Abstract: Objective-Adhesion of monocytes to endothelium can be supported by monocyte-monocyte interactions resulting in the formation of cell aggregates at the vessel wall (clusters). Since platelets that are bound to the injured vessel wall support monocyte adhesion and platelet activation in the circulation leads to formation of platelet-monocyte complexes (PMCs), we examined whether adhesion of PMCs to the vessel wall enhances monocyte clustering. Methods and Results-The effect of PMC formation in monocyte adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 25 publications
8
54
0
1
Order By: Relevance
“…Perfusion experiments were performed as described previously (25). In short, 1 million neutrophils were perfused through a HUVEC monolayer-containing chamber.…”
Section: Neutrophil Isolation and Pretreatment In Rolling Assaysmentioning
confidence: 99%
“…Perfusion experiments were performed as described previously (25). In short, 1 million neutrophils were perfused through a HUVEC monolayer-containing chamber.…”
Section: Neutrophil Isolation and Pretreatment In Rolling Assaysmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Moreover, activated platelets can indirectly support leukocyte recruitment via formation of platelet-leukocyte aggregates (PLAs). 25 Through P-selectin, platelets bind to the P-selectin glycoprotein ligand on leukocytes, and the multicellular conjugates produce chemokines, such as CCL2 and CCL5, and cytokines, such as interleukin-1␤ (IL-1␤), to further activate leukocytes. [23][24][25][26][27][28] In vitro observations have indicated that these conjugates tether and roll on endothelial cells with a higher avidity than nonconjugated leukocytes, thereby enhancing endothelial activation.…”
Section: Introductionmentioning
confidence: 99%
“…25 Through P-selectin, platelets bind to the P-selectin glycoprotein ligand on leukocytes, and the multicellular conjugates produce chemokines, such as CCL2 and CCL5, and cytokines, such as interleukin-1␤ (IL-1␤), to further activate leukocytes. [23][24][25][26][27][28] In vitro observations have indicated that these conjugates tether and roll on endothelial cells with a higher avidity than nonconjugated leukocytes, thereby enhancing endothelial activation. [26][27][28] In addition, PLAs have been observed in prethrombotic or prothrombotic clinical conditions, and may provide a suitable predictor of acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…It mediates the adhesion of activated platelets to neutrophils and monocytes via a specific interaction with P-selectin glycoprotein-1 5,23,24 and may trigger multiple intracellular events within leukocytes to promote vascular inflammation and facilitate atherosclerosis and thrombosis. [24][25][26][27] Clinically, an increased expression of platelet P-selectin has been shown in patients with atherothrombotic diseases, including those in the acute phase of ischemic stroke 28 and with acute coronary syndrome. 29,30 However, determination of platelet P-selectin and studies of platelet-monocyte interaction have not been performed in patients with TA.…”
Section: Discussionmentioning
confidence: 99%